If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 + -1w = 294 Solving 86 + -1w = 294 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-86' to each side of the equation. 86 + -86 + -1w = 294 + -86 Combine like terms: 86 + -86 = 0 0 + -1w = 294 + -86 -1w = 294 + -86 Combine like terms: 294 + -86 = 208 -1w = 208 Divide each side by '-1'. w = -208 Simplifying w = -208
| 14.9=8.6/.9m | | -y+289=201 | | 50000m=m | | 2=3-2 | | y^3-3*Y-1=0 | | .9m=14.9-8.6 | | 1/5x-7/2x=1 | | 3a^7(a+9)(a-1)= | | .9=14.9-8.6 | | 32=8+4y | | 6(2-x)-(x+3)=3(-x+1) | | 2a+36=112 | | 30x+115=985 | | -8x-1=3x^2+2 | | 21+2x=57 | | 6tanx-1=0 | | 4(a+3)=12 | | 9x+14=112 | | 2r^5-6r^4=56r^3 | | 3x+2=4x^2 | | (3x-7)-25=0 | | 13x=585 | | 6(k-7)=18 | | X-83=29 | | 21=-d+3-d | | 4(k+5)=32 | | 7w=17 | | 18x^2+29x+3=0 | | 4(c+3)=36 | | 6m-10=62 | | 11x+1y=53 | | 400-8n=2800 |